1, 4‐Benzoquinone Derivatives for Enhanced Bioelectrocatalysis by Fructose Dehydrogenase from Gluconobacter Japonicus: Towards Promising D‐Fructose Biosensor Development. Issue 5 (7th January 2020) - Voitechovič, Edita; Vektarienė, Aušra; Vektaris, Gytis; Jančienė, Regina; Razumienė, Julija; Gurevičienė, Vidutė
Abstract: D‐fructose amount in food and beverages should be carefully controlled in order to avoid its overconsumption by human, which can lead to various metabolic diseases. Thus, the development of a low‐cost and portable (bio)sensors, which realize the on‐site monitoring of D‐fructose, is still highly required. In this work, we proposed several reagentless bioelectrochemical systems (BioESs) based on fructose dehydrogenase EC1.1.99.11 from Gluconobacter japonicus (FDH) and on 2‐arylamine‐1, 4‐benzoquinone (ABQ) derivatives as a platform for the development of D‐fructose electrochemical biosensor. To design a reliable and easily reproducible BioES, we used the simple physical sorption as the electrode modification strategy for ABQs and FDH immobilization that is suitable for low‐cost mass production of the biosensors by standard microfabrication techniques. To choose the most suitable ABQ compounds for BioESs design, we proposed a novel theoretical approach of potential ET mediator evaluation through its electrochemical properties. A set of newly synthesized and of previously applied ABQs was characterized both electrochemically and using the density functional theory (DFT). It was shown that results obtained by quantum chemical analysis were in a good agreement with the ABQ characteristics obtained in electrochemical measurements. We suggest that the calculated local ionization energy values and theoretical redox potential obtained by DFT are a powerful tool for prediction of ABQs electrochemical properties. The performance of the BioESs with FDH under study was determined by electrochemical and electronic properties of ABQ derivatives and FDH orientation and stabilization on the electrode surface. The most promising BioES was based on carbon paste electrodes and 2‐(3‐nitro(phenyl)amino)‐ cyclohexa‐2, 5‐dien‐1, 4‐dione as ET mediator, which accelerated FDH catalysis and improved its stability better, then other studied ABQs. The bioelectrocatalytic process was characterized by initial apparent maximum current density of 7.1 μA cm −2 at the optimal conditions (+400 mV vs. Ag/AgCl, McIlvaine's buffer, pH 5.0 and 20 °C). The findings of this research open new possibilities for development of cost‐effective biosensors with FDH and, potentially, with other redox enzymes. Abstract :